2017
DOI: 10.3390/safety3010009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Beginner Driver Education in Oregon

Abstract: Abstract:Although driver education (DE) is widely accepted as an effective teen driver safety measure and widely available in the United States, Canada and elsewhere, evaluations have generally failed to show that such formal programs actually produce safer drivers. To address the issue of safety effects as part of a larger investigation, two studies were conducted to examine whether the Oregon Department of Transportation (ODOT)-approved DE program was associated with reductions in collisions and convictions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 16 publications
1
24
1
Order By: Relevance
“…This study builds on recent findings by Mayhew et al (2014). A key difference between this study and Mayhew et al concerns the role of driver education within the graduated licensing environment.…”
Section: The Present Studymentioning
confidence: 71%
See 4 more Smart Citations
“…This study builds on recent findings by Mayhew et al (2014). A key difference between this study and Mayhew et al concerns the role of driver education within the graduated licensing environment.…”
Section: The Present Studymentioning
confidence: 71%
“…They suggested that teen drivers lacked knowledge of how to handle the full range of driving situations and that parental training during the supervised training period (log) may vary in comprehensiveness and quality. Mayhew et al (2014) found that teens taking driver education had higher scores on tests of these types of knowledge as well as better performance on tests of driving skills. Their findings suggest that formal driver education may provide a more thorough and consistent training and instruction than informal parent or adult training, thereby accelerating teens' learning and better preparing them for unsupervised driving.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations